The governorship of Sir William Robinson in the Straits Settlements : 1877-1879 - Tham Junean,; Mohd Samsudin,; Suffian Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Sir William Robinson was the Governor of the Straits Settlements from October 1877 to February 1879. Robinson’s presence in Malaysian history is practically non-existent, because of the dismissive statements of later commentators and the short length of his tenure. Robinson’s relish of the governor’s ceremonial role also contributed to his unpopularity by making him seem distant to the Straits community. Politically, Robinson continued the policy of indirect rule in the Malay States. However, he had concerns about its stability and the authority of the Residents in administering, preferring instead a policy of annexation. However, his suggestions were politely set aside by a Colonial Office resistant to change and also by the differing Malay States policy of his successor, Sir Frederick Weld. Conducted using qualitative methods, this research also used a wide range of primary sources including Colonial Office and Admiralty records, government gazettes, newspapers, and private correspondence. This study presents a more in-depth assessment of Robinson’s contribution to Malaysian history, and finds that, despite Robinson’s uncontroversial and smooth governance of the colony, the failure of his annexation policy in the Malay States overshadowed his achievements, making his tenure seem undistinguished.